2012
DOI: 10.1387/ijdb.113454ab
|View full text |Cite
|
Sign up to set email alerts
|

Hydra, a model system to trace the emergence of boundaries in developing eumetazoans

Abstract: In developing embryos, boundary formation between neighbouring groups of cells is essential to establish compartments which later fulfil specialized functions. The ability to form such boundaries has likely developed early in animal evolution -due to functional requirements imposed by the necessity to separate tissues which protect the animal, take up food or ensure propagation. Essential for boundary formation are local cues which may be provided by the intersection of diffusible molecules or set locally by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 69 publications
0
22
0
1
Order By: Relevance
“…1). The boundaries of the corresponding body regions, where terminal differentiation occurs, are defined by the expression of genes that act in positiondependent differentiation (see Böttger and Hassel, 2012). Regeneration experiments and tracking of GFP-positive epithelial cells in transgenic polyps have demonstrated that every proliferating cell of the body column has the potential to give rise to all three types of differentiated cells (Wittlieb et al, 2006).…”
Section: Ectodermal Epithelial Cellsmentioning
confidence: 99%
“…1). The boundaries of the corresponding body regions, where terminal differentiation occurs, are defined by the expression of genes that act in positiondependent differentiation (see Böttger and Hassel, 2012). Regeneration experiments and tracking of GFP-positive epithelial cells in transgenic polyps have demonstrated that every proliferating cell of the body column has the potential to give rise to all three types of differentiated cells (Wittlieb et al, 2006).…”
Section: Ectodermal Epithelial Cellsmentioning
confidence: 99%
“…The mouth and tentacles are called the hydranth (Holdway, 2005). The rest of this organism is known as the column and has four distinctive sections: the gastric section located between the tentacles and the first (apical) bud; the budding section which produces the buds; the peduncle which is located between the lowest bud and basal disc and the basal disc which is the foot-like formation (Holdway, 2005; see also in this issue Böttger and Hassel, 2012). This structural complexity, simpler than vertebrates with central nervous system and specialized organs, but more complex than cultured cells, makes Hydra comparable to a living tissue whose cells and distant regions are physiologically connected (Galliot et al, 2006).…”
Section: Hydra Anatomymentioning
confidence: 99%
“…This gives the opportunity to examine the outcomes of energy allocation upon various environmental stresses on the fitness of Hydra. Under asexual reproduction Hydra that are well fed use the excess of cells that are produced by forming buds in the middle of their body (Müller, 1996;Böttger and Hassel, 2012). The ability of Hydra to regenerate is due to the constantly proliferating epithelial and interstitial cells in its body column, in the absence of bisection this constant cell renewal allows the animal to bud at a rapid rate (Hoffmeister-Ullerich, 2007).…”
Section: Reproductionmentioning
confidence: 99%
“…The maturation step is clearly detectable by in situ hybridization experiments for structural molecular components of the nematocyst , Engel et al, 2001. Gene expression for these molecules is restricted to the body column of the animal and terminated at a sharp border below the head (see also in this issue Böttger and Hassel, 2012). In the tentacles mature nematocysts are incorporated into large battery cells that harbor several types of capsules in a close arrangement (Fig.…”
mentioning
confidence: 98%